We need to promote research in doctoral program in public health (Revista Venezolana de Salud Pública, 2018)
It discusses the importance of knowing the intention of studying reality, for it is about showing how this process of knowing depends on the philosophical foundation that supports this intention. This particular form of knowledge production is a scientific theory and a deep reflection on the phenomenon paradigmatic linked the researcher has dealt with the conscious of postures oriented in their work. Therefore, selecting a research topic means implicitly define a line of work, supported by a body of knowledge of a group of researchers who share an epistemological methodology oriented in a working line. Consequently, this paper tries to establish links between what should be a knowledge production with an epistemological position, generated doctoral studies and the complex relationship between science and technology and society.
Keywords: Knowledge; Epistemology; Public Health; Interdisciplinary